LOWER AND MIDDLE CALLOVIAN GASTROPOD ASSEMBLAGES FROM CENTRAL EUROPEAN RUSSIA - Guzhov A.V. (My University, 2006)
Two gastropod assemblages from the Lower Callovian of the Kostroma Region and the Middle Callovian of the Yaroslavl' Region are studied and compared with synchronous assemblages of the Kostroma, Moscow, Bryansk, and Kursk regions. It is suggested that gastropods from the Yaroslavl' and Kostroma regions inhabited colder water basins than gastropods from more southern regions. A new genus and species Znamenkiella ovalis gen. et sp. nov. (family Pseudomelaniidae) are described from the Lower Callovian of the Kostroma Region. © Pleiades Publishing, Inc. 2006.
Keywords: CALLOVIAN; GASTROPOD ASSEMBLAGES; GASTROPOD PALEOBIOGEOGRAPHY; GASTROPODA; PSEUDOMELANIIDAE; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский